Shifting from Theory to Practice: EFL Student Teachers’ Readiness in Online Practicum - Syarifah, Hikmatus; Fadhilah, Ma'rifatul (Institut Agama Islam Negeri Ponorogo, 2022)
A practicum is a study program designed to prepare pre-service teachers where they apply the theory they have learned previously. This practicum also intends to give pre-service teachers a chance to practice their teaching skills. Pre-service teachers are affected significantly by the shift from offline to online learning. The goal of this research was to discover the reflective practices of EFL pre-service teachers’ readiness in an online practicum, particularly their readiness to use technology in their learning. This research is qualitative research with a case study approach. The setting of this research is an online practicum at the Department of English Education, Walisongo State Islamic University Semarang. The participants in this research were pre-service teachers who took part in an online practicum. Seven pre-service teachers who teach English participated in this research. The data collected through reflective practice guided by the Gibbs reflective cycle was then analyzed using thematic analysis. The results of this research revealed that the participants had no problem with technology because they were used to using technology in their daily life and also in their learning life as well as pedagogical and professional aspects.